Getting Out of Language Cocoon: Cognitive Defusion - Ahmet Nalbant; Kaasim Fatih Yavuz (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Treating thoughts directly in psychotherapies was disregarded until development of Cognitive Therapies. So-called distorted or irrational thoughts that are claimed to contribute psychopathology are subjected to Cognitive Therapies. In sessions, cognitive therapists try to help clients to change those thoughts or help them to find alternatives. Various advancements in psychotherapy field started discussions about trying to change thoughts directly in psychotherapy. After development of Cognitive Therapies, recent years have witnessed development of third wave psychotherapies and those psychotherapies made it possible to treat thoughts in different ways. Rather than focusing on content, these psychotherapies aim to help clients to develop skills for distancing from thoughts or for looking at those thoughts. Acceptance and Commitment Therapy (ACT), is a third wave therapy and ACT does not treat thoughts as distorted or wrong. ACT has its roots from philosophical background called Functional Contextualism and according to this, one needs to understand the function of a thought in a given context. From this point of view, ACT uses defusion techniques to help clients distancing from thoughts that following them is not workable in various contexts. In this paper, we tried to summarize defusion techniques with their theoretical background and we also gave examples of how to use them in therapy room and mentioned about their scientific support. [JCBPR 2019; 8(1.000): 58-62]